2020
DOI: 10.1002/esp.4959
|View full text |Cite
|
Sign up to set email alerts
|

Sediment detachment in piping‐prone soils: Cohesion sources and potential weakening mechanisms

Abstract: Soil piping is a widespread land degradation process that may lead to gully formation. However, the processes involved in sediment detachment from soil pipe walls have not been well studied, although their recognition is a crucial step to protect soils from piping erosion. This study aims to recognize the factors affecting cohesion and to identify the mechanisms which are likely to be responsible for the disintegration of soil. The study has been conducted in mid-altitude mountains under a temperate climate (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
(134 reference statements)
1
16
0
Order By: Relevance
“…The lower values of ER and higher values of EC a in deeper layers may be connected to higher water and clays content that increases down the undisturbed soil profile (not affected by piping). These trends in soil profiles have been recently presented by Bernatek‐Jakiel et al (2020) in the vicinity of the plot analyzed in this study. This is connected with the water table which occurs at the depth of 1–1.1 m.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The lower values of ER and higher values of EC a in deeper layers may be connected to higher water and clays content that increases down the undisturbed soil profile (not affected by piping). These trends in soil profiles have been recently presented by Bernatek‐Jakiel et al (2020) in the vicinity of the plot analyzed in this study. This is connected with the water table which occurs at the depth of 1–1.1 m.…”
Section: Discussionsupporting
confidence: 86%
“…They observed that the highest measurement accuracy was obtained at the highest tested soil moisture (i.e., 24.5%). In the study area, the soil moisture is generally above 30% (Bernatek‐Jakiel et al, 2020), which may suggest sufficient measurement accuracy.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a recent study quantified rainfall thresholds for gully initiation (Zhao et al, 2021), which could inform prevention activities such as drainage design. Underscoring the importance of hydrology and soil erodibility, recent research has identified soil saturation as a cause of piping erosion through loss of soil cohesion (Bernatek‐Jakiel et al, 2020). Consistent with that finding, soil pipe sediment yields have been found to be dependent on detachment rather than on runoff rate; and on supply rather than transport capacity (Wilson et al, 2020).…”
Section: Is Gully Research Good Enough To Inform Management and Preve...mentioning
confidence: 99%
“…The result of these extreme flow conditions is not only high sediment detachment and transport capacity, but also frequent mass failures of aggregates from pipe sidewalls and roofs. However, limited research has been conducted on particle and aggregate detachment (Bernatek-Jakiel et al, 2020) within soil pipes. Bernatek-Jakiel et al (2020) conducted the most detailed study to date on the effects of fluid chemistry on particle and aggregate detachment in soil pipes formed in cohesive soils.…”
Section: Introductionmentioning
confidence: 99%
“…However, limited research has been conducted on particle and aggregate detachment (Bernatek-Jakiel et al, 2020) within soil pipes. Bernatek-Jakiel et al (2020) conducted the most detailed study to date on the effects of fluid chemistry on particle and aggregate detachment in soil pipes formed in cohesive soils. Their experiments involved flooding undisturbed soil samples with different solutions to determine the role of fluid properties on soil cohesion losses as well as air slaking.…”
Section: Introductionmentioning
confidence: 99%